Saluran Distribusi Pemasaran Asuransi - Indah Ussania; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
Product distribution is one of the marketing process's activities. Many product manufacturers do not sell to end users directly. This is due to the fact that cost distribution is typically the primary reason corporations do not sell items to end customers. The marketing channel is in charge of getting the product from the manufacturer (the insurance company) to the consumer/customer. This can overcome the owner of a product or service's isolation from the people who require it in terms of time, location, and property. This marketing channel, in reality, necessitates product marketing channel management in compliance with OJK standards. In addition, any rivalry that emerges in the marketing channel while selling insurance goods. As a result, the goal of this article is to go into detail about the marketing channels for insurance products in public marketing. Keywords: Marketing Channels, Distribution, Insurance